Achieving gender equality through challenging social norms: BRAC’s Polli Shomaj program - Qayum, Nayma; Hassan, Mirza; Aziz, Syeda Salina (Brac University, 2024)
This article was published in The Development in Practice [©2023 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/09614524.2023.2220989 The Article's website is at: https://www.tandfonline.com/doi/permissions/10.1080/09614524.2023.2220989?scroll=top